Future skills : Developing skills for jobs that do not yet exist in sectors that have not yet been invented - Alasdair White (Penerbit Universiti Kebangsaan Malaysia, 2022)
In this paper, the author reconsiders the question of whether compulsory education systems are ‘fit for purpose’, when the purpose is to provide adequately educated people with the Knowledge, Skills, and Attributes (KSAs) that allow them to be useful and productive members of society. By the use of structural unemployment rates, the author shows that even though the populations were increasing, unemployment remained the same over a long period suggesting that the right KSAs were being provided. The author then considers the changes to compulsory education that occurred in the last two decades of the 20th century in medium and high-income societies, and how this has, potentially, broken the link between the KSAs provided and the KSAs needed. He ends with a call for action to rethink the provision of tertiary education so as to ensure those experiencing it are fitted with the skills needed for the future. This paper was delivered as the keynote opening speech at the iCiTRA conference in Malaysia in September 2021, the text itself is taken from the author’s 2017 paper Unfit for Purpose? Graduate business education and the real world: a reflective and evidence-based discussion about education, jobs and unemployment.